Plugging material with slow release and dispersion effects as well as preparation method and application of plugging material

By designing the core and shell structure in the leak-blocking material, the sustained release effect of silica porous microspheres and polyacrylamide is used to solve the problem of increased viscosity after injection into the wellbore, and the smooth flow of the leak-blocking slurry is achieved. Efficient leakage plugging effect.

CN119307241AActive Publication Date: 2025-01-14PETROCHINA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310862715.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-14
Estimated Expiration
2043-07-13

AI Technical Summary

Technical Problem

The viscosity of existing leak-blocking materials increases after injection into the wellbore and the fluidity becomes worse, resulting in the amount of solid-phase particles reaching the leakage layer. The increase in solid-phase particles to block the cracks will lead to an increase in the density of leak-blocking slurry and fracturing the well walls. The risk of the virus forms a vicious cycle.

Method used

Use leak-blocking materials with sustained release dispersion, which include core and shell structures. The core is porous silica microspheres and polyacrylamide, starch bonding layer and resin protective layer. The shell is clay and inorganic particles, and will not increase in the initial stage. The viscosity of the leak-blocking slurry is as the shell falls off under sinking and high-temperature environments, the core is exposed, and the release of polyacrylamide increases viscosity and dispersion.

Benefits of technology

The leakage plugging slurry flows smoothly underground, reduces the initial viscosity of the leakage plugging slurry, extends the suspension time of solid phase particles, improves the leakage plugging effect, and avoids the risk of fracturing the well wall of the leakage plugging slurry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004338608080000081
    Figure BDA0004338608080000081
Patent Text Reader

Abstract

The invention provides a leaking stoppage material with slow release and dispersion effects as well as a preparation method and application thereof, the leaking stoppage material comprises an inner core and a shell in a mass ratio of (4-5): 1, the inner core comprises silicon dioxide porous microspheres, polyacrylamide is adhered to the interiors of pores of the silicon dioxide porous microspheres, and the mass ratio of the silicon dioxide porous microspheres to the polyacrylamide is 1: (16-18); the shell is formed by mixing clay and inorganic particles. The plugging material disclosed by the invention has slow release and dispersion effects, the viscosity of the plugging slurry is not increased when the plugging material just enters a well, and the viscosity of the plugging slurry is slowly increased only in a sinking process, so that a plugging effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plugging materials, and in particular to a plugging material with a slow-release dispersion effect, a preparation method and an application thereof. Background Art

[0002] Well leakage is a common complex situation in drilling projects. Most drilling processes have different degrees of leakage. Severe well leakage will cause the pressure in the well to drop, affecting normal drilling, causing wellbore instability, inducing formation fluid to flow into the wellbore and blowout. The cause of well leakage is usually that the pressure of the liquid column in the wellbore is greater than the formation pressure; the formation has large pores, good permeability, and the presence of caves and cracks.

[0003] After a well leak occurs, plugging materials need to be lowered to plug the leak and seal the cracks in the well wall. However, there is a problem with conventional plugging materials. Since high molecular polymers need to be added to the plugging materials to suspend and disperse the solid phase particles, after configuring them into plugging slurry, the high molecular polymers increase the viscosity of the plugging slurry and deteriorate its fluidity. After being injected into the wellbore, the amount of solid phase particles that can effectively reach the cracks in the leakage layer is very small. Therefore, an excess amount of solid phase particles needs to be added to ensure that the cracks are blocked. However, too much solid phase particles will increase the density of the plugging slurry. When the density of the plugging slurry increases, there will be a risk of fracturing the well wall, resulting in a vicious cycle of more plugging and more leakage. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a plugging material with slow-release dispersion effect and its preparation method and application, so that the plugging material will not increase the viscosity of the plugging slurry when it is just entered into the well, and will slowly increase the viscosity of the plugging slurry during the sinking process, thereby exerting the plugging effect.

[0005] To achieve the above object, the present invention provides a plugging material with a slow-release dispersion effect, which comprises a core and a shell in a mass ratio of (4-5):1;

[0006] The inner core includes porous silica microspheres, and polyacrylamide is adhered to the pores of the porous silica microspheres, wherein the mass ratio of the porous silica microspheres to the polyacrylamide is 1:(16-18);

[0007] The shell is formed by mixing clay and inorganic particles.

[0008] In the above-mentioned plugging material with slow-release dispersing effect, preferably, the porous silica microspheres have a porous capillary structure; and the particle size of the porous silica microspheres is 0.3-0.5 mm.

[0009] In the above-mentioned plugging material with slow-release dispersing effect, preferably, the polyacrylamide is in powder form.

[0010] In the above-mentioned plugging material with slow-release dispersing effect, preferably, the core further comprises a starch bonding layer and / or a resin protective layer coated on the surface of the porous silica microspheres.

[0011] In the above-mentioned plugging material with slow-release dispersing effect, preferably, the inner core further comprises from the inside to the outside: a starch bonding layer and a resin protective layer coated on the surface of the porous silica microspheres.

[0012] In the above-mentioned plugging material with slow-release dispersing effect, preferably, the mass ratio of the porous silica microspheres, the starch bonding layer, and the resin protective layer is 1:(20-24):(59-62).

[0013] In the above-mentioned plugging material with slow-release dispersing effect, preferably, the resin protective layer comprises paraffin and water-absorbing resin in a mass ratio of (30-34): (26-28).

[0014] In the above-mentioned plugging material with slow-release dispersing effect, preferably, the water-absorbing resin is sodium polyacrylate.

[0015] In the above-mentioned plugging material with slow-release dispersing effect, preferably, the shell is a fully enclosed structure; the mass ratio of clay and inorganic particles in the shell is (40-45):(15-18).

[0016] In the above-mentioned plugging material with slow-release dispersing effect, preferably, the inorganic particles contain calcium carbonate powder.

[0017] In the above-mentioned plugging material with slow-release dispersing effect, preferably, the particle size of the inorganic particles is 10-16 μm.

[0018] The present invention also provides a method for preparing the above-mentioned plugging material with slow-release dispersing effect, which comprises the following steps:

[0019] Preparation of porous silica microspheres;

[0020] Allowing polyacrylamide to load into the pores of the porous silica microspheres to obtain an inner core;

[0021] The paste containing clay and inorganic particles is coated on the surface of the inner core and dried to obtain the plugging material with slow-release dispersion effect.

[0022] In the above-mentioned method for preparing the plugging material with slow-release dispersion effect, preferably, the method for preparing the porous silica microspheres comprises the following steps:

[0023] A first reaction is carried out between dimethyldichlorosilane and hydrochloric acid to obtain an oily substance;

[0024] Allowing the oil to undergo a second reaction with aqueous ammonia, filtering out a solid product, and obtaining semi-finished microspheres;

[0025] The semi-finished microspheres are calcined and cooled to obtain the porous silica microspheres.

[0026] In the above-mentioned method for preparing the plugging material with slow-release dispersing effect, preferably, the method for preparing the porous silica microspheres further comprises: after the second reaction, washing the filtered solid product with anhydrous ethanol.

[0027] In the preparation method of the above-mentioned plugging material with slow-release dispersing effect, preferably, the mass ratio of dimethyldichlorosilane to hydrochloric acid is (45-55):(15-20); and the mass concentration of the hydrochloric acid is 42-48wt%.

[0028] In the above method for preparing the plugging material with slow-release dispersing effect, preferably, the reaction temperature of the first reaction is 40-50° C., and the reaction time is 30-40 min.

[0029] In the preparation method of the above-mentioned plugging material with slow-release dispersing effect, preferably, the mass ratio of the oily substance to the ammonia water is (20-30):(8-10); and the mass concentration of the ammonia water is 28-32wt%.

[0030] In the above method for preparing the plugging material with slow-release dispersing effect, preferably, the reaction temperature of the second reaction is 35-38° C., and the reaction time is 20-25 min.

[0031] In the method for preparing the plugging material with slow-release dispersing effect, preferably, the calcination temperature is 500-700° C. and the calcination time is 60-70 min.

[0032] In the above-mentioned method for preparing the plugging material with slow-release dispersing effect, preferably, the method for preparing the porous silica microspheres further comprises: washing the filtered solid product with anhydrous ethanol.

[0033] In the above-mentioned method for preparing the plugging material with sustained-release dispersing effect, preferably, the method for preparing the plugging material with sustained-release dispersing effect further comprises: fully contacting the porous silica microspheres loaded with polyacrylamide with starch powder and then wetting them to obtain the inner core.

[0034] In the above method for preparing the plugging material with slow-release dispersing effect, preferably, the method for preparing the plugging material with slow-release dispersing effect further comprises: fully contacting the silica porous microspheres loaded with polyacrylamide with a molten mixture of paraffin and water-absorbing resin to obtain the inner core.

[0035] The present invention also provides the plugging material with slow-release dispersing effect or the plugging material with slow-release dispersing effect obtained from the plugging material with slow-release dispersing effect and its application in drilling plugging.

[0036] The plugging material with slow-release dispersing effect provided by the present invention comprises a core and an outer shell, and the outer shell is a fully enclosed structure, which can effectively coat the porous silica microspheres inside it. When preparing the plugging slurry and just injecting it into the wellbore, the viscosity of the plugging slurry will not increase; as the plugging material descends, due to long-term immersion, the outer shell falls off, exposing the disintegrating inner shell inside it, and because the disintegrating inner shell is made of paraffin and water-absorbing resin, it begins to dissolve and fall off in the high-temperature environment underground, gradually exposing the inner core, and the powdered polyacrylamide in the porous silica microspheres is released to increase the viscosity of the plugging slurry, thereby improving the suspension and dispersibility of the solid phase particles as the main plugging material, and the porous silica microspheres and inorganic particles can act as solid phase particles to participate in plugging.

[0037] In addition, since the porous silica microspheres have a porous capillary structure, when the outer shell falls off and the inner core is exposed, the powdered polyacrylamide is in the pores of the porous silica microspheres, which slows down the loss rate and achieves a slow-release and long-lasting effect. In addition, there is starch paste in the pores, which further slows down the loss rate of the powdered polyacrylamide, that is, it can maintain the high viscosity state of the plugging slurry near the leakage layer for a long time.

[0038] The technical solution provided by the present invention has the following beneficial effects:

[0039] The plugging material with slow-release dispersing effect prepared by the present invention comprises a core and an outer shell. The outer shell is a fully enclosed structure, which can effectively cover the inner core. When preparing the plugging slurry and just injecting it into the wellbore, the viscosity of the plugging slurry will not increase, so that the plugging slurry can flow smoothly underground. After continuous immersion, when the plugging material drops to the vicinity of the leakage layer, the outer shell will gradually fall off, releasing the powdered polyacrylamide in the core to increase the viscosity of the plugging slurry, thereby improving the suspension and dispersibility of the solid phase particles as the main plugging material. The core and inorganic particles can act as solid phase particles to participate in plugging; in addition, since the core is a porous capillary structure, when the outer shell falls off and the core is exposed, the powdered polyacrylamide in the pores of the core slows down the loss rate, achieving a slow-release and long-lasting effect, that is, it can maintain the high viscosity state of the plugging slurry near the leakage layer for a long time. DETAILED DESCRIPTION

[0040] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0041] Example 1

[0042] This embodiment provides a method for preparing a plugging material with a slow-release dispersion effect, comprising the following steps:

[0043] S1. Prepare porous silica microspheres with porous capillary structure and control the particle size to 0.5 mm:

[0044] S11, pouring 50 parts by weight of dimethyldichlorosilane into a beaker, adding 18 parts by weight of 45 wt% concentrated hydrochloric acid into the beaker, stirring at 45° C. for 35 minutes to obtain oily octamethylcyclotetrasiloxane;

[0045] S12, taking 25 parts by weight of the octamethylcyclotetrasiloxane obtained in step S11, mixing it with 9 parts by weight of 30 wt% ammonia water, heating and stirring at 37° C. for 22 min, filtering, washing with anhydrous ethanol to obtain octamethylcyclotetrasiloxane polymerized microspheres;

[0046] S13, calcining the octamethylcyclotetrasiloxane polymerized microspheres obtained in step S12 at a temperature of 600° C. for 65 min, taking out and cooling naturally to obtain porous silica microspheres; the porous silica microspheres have a porous capillary structure and a particle size of 0.5 mm;

[0047] S2. Preparation of kernel:

[0048] S21, taking 1 part by weight of the porous silica microspheres obtained in step S13, putting them into a container containing powdered polyacrylamide, vibrating and stirring, and then taking them out to obtain a first treated product, wherein the first treated product contains 17 parts by weight of powdered polyacrylamide;

[0049] S22, then transferring the first treated product to a container containing starch powder and vibrating and stirring, taking it out and transferring it to a clean container, sprinkling it with clean water, and draining it naturally to obtain a second treated product, wherein the second treated product contains 22 parts by weight of starch;

[0050] S23, after melting paraffin, adding sodium polyacrylate water-absorbing resin thereto to obtain a melt, wherein the mass ratio of paraffin and sodium polyacrylate water-absorbing resin in the melt is, for example, 32:27; putting the second treated product into the melt and rolling and stirring, taking it out and draining it naturally, to obtain a kernel, the kernel containing 32 parts by weight of paraffin and 27 parts by weight of sodium polyacrylate water-absorbing resin;

[0051] S3. Mix 42 parts by weight of clay, 17 parts by weight of calcium carbonate powder (particle size 13 μm) and 13 parts by weight of water to form a paste, take 5 parts by weight of the core obtained in step S23 and put it into the paste, mix and stir for 5 minutes, then take it out, drain, and dry it to obtain plugging material A1. The obtained plugging material A1 includes an outer shell and an inner core, and the mass ratio of the outer shell to the inner core is 1:4.6.

[0052] Example 2

[0053] This embodiment provides a method for preparing a plugging material with a slow-release dispersion effect, comprising the following steps:

[0054] S1. Prepare porous silica microspheres with porous capillary structure, and control the particle size to 0.4 mm:

[0055] S11, pouring 45 parts by weight of dimethyldichlorosilane into a beaker, adding 15 parts by weight of 45 wt% concentrated hydrochloric acid into the beaker, stirring at 40° C. for 30 min to obtain oily octamethylcyclotetrasiloxane;

[0056] S12, taking 20 parts by weight of the octamethylcyclotetrasiloxane obtained in step S11, mixing it with 8 parts by weight of 30 wt% ammonia water, heating and stirring at 35° C. for 20 min, filtering, washing with anhydrous ethanol to obtain octamethylcyclotetrasiloxane polymerized microspheres;

[0057] S13, calcining the octamethylcyclotetrasiloxane polymerized microspheres obtained in step S12 at a temperature of 500° C. for 60 min, taking out and cooling naturally to obtain porous silica microspheres; after testing, the porous silica microspheres have a porous capillary structure and a particle size of 0.4 mm;

[0058] S2. Preparation of kernel:

[0059] S21, taking 1 part by weight of the porous silica microspheres obtained in step S13, putting them into a container containing powdered polyacrylamide, vibrating and stirring, and then taking them out to obtain a first treated product, wherein the first treated product contains 16 parts by weight of powdered polyacrylamide;

[0060] S22, then transferring the first treated product to a container containing starch powder and vibrating and stirring, taking it out and transferring it to a clean container, sprinkling it with clean water, and draining it naturally to obtain a second treated product, wherein the second treated product contains 20 parts by weight of starch;

[0061] S23, after melting paraffin, adding sodium polyacrylate water-absorbing resin thereto to obtain a melt, wherein the mass ratio of paraffin and sodium polyacrylate water-absorbing resin in the melt is, for example, 15:13; putting the second treated product into the melt and rolling and stirring, taking it out and draining it naturally, to obtain a kernel, the kernel containing 30 parts by weight of paraffin and 26 parts by weight of sodium polyacrylate water-absorbing resin;

[0062] S3, 40 parts by weight of clay, 15 parts by weight of calcium carbonate powder (particle size 10 microns) and 12 parts by weight of water are mixed into a paste, 5 parts by weight of the core obtained in step S23 are added to the paste and mixed and stirred for 3 minutes, then taken out and drained, and then dried to obtain plugging material A2, which includes an outer shell and an inner core, and the mass ratio of the outer shell to the inner core is 1:5.

[0063] Example 3

[0064] This embodiment provides a method for preparing a plugging material with a slow-release dispersion effect, comprising the following steps:

[0065] S1. Prepare porous silica microspheres and control their particle size to 0.6 mm:

[0066] S11, pouring 55 parts by weight of dimethyldichlorosilane into a beaker, adding 20 parts by weight of 45 wt% concentrated hydrochloric acid into the beaker, stirring at 50° C. for 40 minutes to obtain oily octamethylcyclotetrasiloxane;

[0067] S12, taking 30 parts by weight of the octamethylcyclotetrasiloxane obtained in step S11, mixing it with 10 parts by weight of 30 wt% ammonia water, heating and stirring at 38° C. for 25 min, filtering, washing with anhydrous ethanol to obtain octamethylcyclotetrasiloxane polymerized microspheres;

[0068] S13, calcining the octamethylcyclotetrasiloxane polymerized microspheres obtained in step S12 at a temperature of 700° C. for 70 min, taking out and cooling naturally to obtain porous silica microspheres; after testing, the porous silica microspheres have a porous capillary structure and a particle size of 0.6 mm;

[0069] S2. Preparation of kernel:

[0070] S21, taking 1 part by weight of the porous silica microspheres obtained in step S13, putting them into a container containing powdered polyacrylamide, vibrating and stirring, and then taking them out to obtain a first treated product, wherein the first treated product contains 18 parts by weight of powdered polyacrylamide;

[0071] S22, then transferring the first treated product to a container containing starch powder and vibrating and stirring, taking it out and transferring it to a clean container, sprinkling it with clean water, and draining it naturally to obtain a second treated product, wherein the second treated product contains 24 parts by weight of starch;

[0072] S23, after melting paraffin, adding a water-absorbing resin thereto to obtain a melt, wherein the mass ratio of paraffin wax to sodium polyacrylate water-absorbing resin in the melt is, for example, 17:14; placing the second treated product into the melt and rolling and stirring, taking it out and draining it naturally, to obtain a kernel, wherein the kernel contains 34 parts by weight of paraffin wax and 28 parts by weight of sodium polyacrylate water-absorbing resin;

[0073] S3, 45 parts by weight of clay, 18 parts by weight of calcium carbonate powder (particle size 16 microns) and 14 parts by weight of water are mixed into a paste, the core obtained in step S23 is put into the paste and mixed and stirred for 7 minutes, then taken out and drained, and then dried to obtain plugging material A3, the obtained plugging material A3 includes an outer shell and an inner core, and the mass ratio of the outer shell to the inner core is 1:4.

[0074] Comparative Example 1

[0075] This comparative example provides a method for preparing a plugging material, which is the same as Example 1, except that the weight portion of the powdered polyacrylamide is 6 parts. A plugging material D1 is obtained.

[0076] Comparative Example 2

[0077] This comparative example provides a method for preparing a plugging material, which is the same as Example 1, except that steps S22 and S22 are omitted, that is, the starch bonding layer and the resin protective layer are not provided, so as to obtain a plugging material D2.

[0078] Comparative Example 3

[0079] This comparative example provides a method for preparing a plugging material, which is the same as that of Example 1, except that step S3 is omitted, that is, no outer shell is provided, to obtain a plugging material D3.

[0080] Experimental example

[0081] The deeper the oil well, the higher its temperature. This experimental example simulates different depths of the oil well at different temperatures.

[0082] Preparation of plugging slurry: by weight, at room temperature, add 100 parts by weight of water, 4 parts by weight of bentonite, and 20 parts by weight of plugging material into an enamel measuring cup, wherein the plugging materials are the plugging materials obtained in the above-mentioned Examples 1-3 and Comparative Examples 1-3, respectively, and stir to obtain six parts of plugging slurry.

[0083] The plugging slurry was heated to 25°C, 50°C and 80°C respectively, and after being fully stirred at different temperatures, its dynamic shear force was measured to indicate its viscosity. The results are shown in Table 1.

[0084] Table 1 Viscosity properties of plugging slurry

[0085]

[0086] It can be seen from the experimental results in Table 1 that for the plugging materials A1-A3 of Examples 1-3, as the temperature increases, the dynamic shear force of the prepared plugging slurry increases. At 25°C, the dynamic shear force of the plugging slurry is only 0.17, indicating that the plugging slurry at this time has good fluidity and can flow smoothly and quickly downhole; when the temperature rises to 50°C, the dynamic shear force of the plugging slurry only increases slightly; when the temperature rises to 80°C, its dynamic shear force reaches 0.43, indicating that the viscosity of the plugging slurry has increased at this time, and the solid phase particles therein can be better suspended and dispersed, thereby improving its plugging effect. It can be seen that the plugging materials prepared in Examples 1-3 of the present invention have a good slow-release dispersion effect with temperature.

[0087] For the plugging material D1 of comparative example 1, since it is simply a mixture of porous silica microspheres and powdered polyacrylamide, the plugging slurry has a high dynamic shear force at the beginning, which will affect the efficiency of the plugging slurry flowing into the well and make it difficult to transport the solid particles to the underground leakage layer.

[0088] The plugging material D2 of comparative example 2 is not provided with a starch bonding layer and a resin protective layer, and the plugging material D3 of comparative example 3 is not provided with a shell. These two situations make the porous silica microspheres exposed to the slurry too early and release polyacrylamide, which increases the viscosity of the plugging slurry too early and affects the plugging effect of the plugging slurry.

[0089] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A plugging material with a slow-release dispersing effect, comprising a core and a shell in a mass ratio of (4-5):1; The inner core includes porous silica microspheres, and polyacrylamide is adhered to the pores of the porous silica microspheres, wherein: The mass ratio of the porous silica microspheres to polyacrylamide is 1:(16-18); The shell is formed by mixing clay and inorganic particles.

2. The plugging material with slow-release dispersing effect according to claim 1, wherein: The porous silica microspheres present a porous capillary structure.

3. The plugging material with slow-release dispersion effect according to claim 1, wherein: The polyacrylamide is in powder form.

4. The plugging material with slow-release dispersing effect according to claim 1, wherein: The inner core further comprises, from the inside to the outside, a starch bonding layer and / or a resin protective layer coated on the surface of the porous silica microspheres.

5. The plugging material with slow-release dispersion effect according to claim 1, wherein: The inner core comprises a starch bonding layer and a resin protective layer coated on the surface of the porous silica microspheres from the inside to the outside.

6. The plugging material with slow-release dispersing effect according to claim 4 or 5, wherein: The mass ratio of the porous silica microspheres, the starch bonding layer and the resin protective layer is 1:(20-24):(59-62).

7. The plugging material with slow-release dispersing effect according to claim 5, wherein: The resin protective layer comprises paraffin wax and water-absorbing resin in a mass ratio of (30-34):(26-28).

8. The plugging material with slow-release dispersing effect according to claim 7, wherein: The water-absorbing resin is sodium polyacrylate.

9. The plugging material with slow-release dispersion effect according to claim 1, wherein: The shell is a fully enclosed structure; the mass ratio of clay and inorganic particles in the shell is (40-45): (15-18).

10. The plugging material with slow-release dispersion effect according to claim 1, wherein: The inorganic particles are calcium carbonate powder; Preferably, the particle size of the inorganic particles is 10-16 μm.

11. A method for preparing the plugging material with slow-release dispersing effect according to any one of claims 1 to 10, comprising the following steps: Preparation of porous silica microspheres; Allowing polyacrylamide to load into the pores of the porous silica microspheres to obtain an inner core; The paste containing clay and inorganic particles is coated on the surface of the inner core and dried to obtain the plugging material with slow-release dispersion effect.

12. The method for preparing the plugging material with slow-release dispersion effect according to claim 11, wherein: The preparation method of the porous silica microspheres comprises the following steps: A first reaction is carried out between dimethyldichlorosilane and hydrochloric acid to obtain an oily substance; Allowing the oil to undergo a second reaction with aqueous ammonia, filtering out a solid product, and obtaining semi-finished microspheres; calcining the semi-finished microspheres and cooling them to obtain the porous silica microspheres; Preferably, the method further comprises: after the second reaction, washing the filtered solid product with anhydrous ethanol.

13. The method for preparing the plugging material with slow-release dispersion effect according to claim 12, wherein: The mass ratio of dimethyldichlorosilane to hydrochloric acid is (45-55):(15-20); the mass concentration of the hydrochloric acid is 42-48wt%.

14. The method for preparing the plugging material with slow-release dispersion effect according to claim 12, wherein: The reaction temperature of the first reaction is 40-50°C, and the reaction time is 30-40min.

15. The method for preparing the plugging material with slow-release dispersion effect according to claim 12, wherein: The mass ratio of the oily substance to the aqueous ammonia is (20-30):(8-10); the mass concentration of the aqueous ammonia is 28-32wt%.

16. The method for preparing the plugging material with slow-release dispersion effect according to claim 12, wherein: The reaction temperature of the second reaction is 35-38° C., and the reaction time is 20-25 min.

17. The method for preparing the plugging material with slow-release dispersion effect according to claim 12, wherein: The calcination temperature is 500-700° C. and the calcination time is 60-70 minutes.

18. The method for preparing the plugging material with slow-release dispersion effect according to claim 12, wherein: The method for preparing porous silica microspheres further comprises: washing the filtered solid product with anhydrous ethanol.

19. The method for preparing the plugging material with slow-release dispersion effect according to claim 11, wherein: The method for preparing the plugging material with slow-release dispersing effect further comprises: fully contacting the silica porous microspheres loaded with polyacrylamide with starch powder and then wetting them to obtain the core.

20. The method for preparing the plugging material with slow-release dispersion effect according to claim 11, wherein: The method for preparing the plugging material with slow-release dispersing effect further comprises: fully contacting the silica porous microspheres loaded with polyacrylamide with the molten mixture of paraffin wax and water-absorbing resin to obtain the inner core.

21. Use of the plugging material with slow-release dispersing effect as claimed in any one of claims 1 to 10 or the plugging material with slow-release dispersing effect obtained by the preparation method as claimed in any one of claims 11 to 20 in plugging well leakage in drilling.

Citation Information

Patent Citations

  • Encapsulated water absorbent polymers as lost circulation additives for aqueous drilling fluids

    CA1267075A

  • A method for preparing a super absorbent material for plugging leaks in oilfield drilling

    CN102268123A

  • Delayed expansion granular plugging agent

    CN108102620A

  • Composition, preparation method and application of high-temperature and high-pressure expandable plugging agent

    CN114479789A

  • Leaking stoppage slurry and preparation method thereof

    CN115895614A